2014
DOI: 10.7850/jkso.2014.19.4.287
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Coastal Upwelling on Phytoplankton Community in the Southern Part of East Sea, Korea

Abstract: 냉수대 발생 전·후의 해양 환경과 식물플랑크톤 군집 구조 및 크기를 파악을 위해 여름철 빈번하게 냉수대가 발 생되는 동해 남부 해역(울산 정자~부산일광In order to understand environment condition and phytoplankton community before and after coastal upwelling, the influences of upwelling events on phytoplankton community were studied at 18 stations located the Southern part of East Sea, Korea from May to August 2013. The surface water masses showed low temperature and high salinity due to upwelling events at coastal stations (A1, B1, C1). Correlation between temperature and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
(24 reference statements)
0
5
0
1
Order By: Relevance
“…Conversely, there was a higher proportion of nanophytoplankton (2.0–20.0 μm) and microphytoplankton (20.0–200.0 μm), which prefer nutrient‐rich environments (Koike et al, ; Lee et al, ; Probyn, ; Tremblay et al, ), and there was a slightly positive relationship between their abundance and coastal upwelling ( y = 13.28ln( x ) + 26.54, r 2 = 0.2376, RMSE = 9.664; and y = 11.21ln( x ) + 20.58, r 2 = 0.1134, RMSE = 12.75, respectively) (Figures b and c). On the basis of the results of previous studies, which have shown that nutrient inflow and the mixing of water masses promotes the growth of large phytoplankton (Arin et al, ; Estrada & Blasco, ), this relationship is likely because of the decreasing stability of the water mass and the increasing supply of nutrients with an increased intensity of coastal upwelling (Kim et al, ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Conversely, there was a higher proportion of nanophytoplankton (2.0–20.0 μm) and microphytoplankton (20.0–200.0 μm), which prefer nutrient‐rich environments (Koike et al, ; Lee et al, ; Probyn, ; Tremblay et al, ), and there was a slightly positive relationship between their abundance and coastal upwelling ( y = 13.28ln( x ) + 26.54, r 2 = 0.2376, RMSE = 9.664; and y = 11.21ln( x ) + 20.58, r 2 = 0.1134, RMSE = 12.75, respectively) (Figures b and c). On the basis of the results of previous studies, which have shown that nutrient inflow and the mixing of water masses promotes the growth of large phytoplankton (Arin et al, ; Estrada & Blasco, ), this relationship is likely because of the decreasing stability of the water mass and the increasing supply of nutrients with an increased intensity of coastal upwelling (Kim et al, ).…”
Section: Resultsmentioning
confidence: 98%
“…To investigate the relationship between the intensity of coastal upwelling along the east coast of Korea in relation to alongshore winds and variation in the size structure of dominant phytoplankton, we performed a correlation analysis between UA and the concentration of different size classes of phytoplankton, as shown in Figure . The proportion of picophytoplankton (0.7–2.0 μm), which prefer nutrient‐poor environments and regenerated nitrogen such as ammonium (Koike et al, ; Lee et al, ; Probyn, ; Tremblay et al, ), tended to slightly decrease as the upwelling intensity increased ( y = −24.43ln( x ) + 52.5, r 2 = 0.2469, root mean square error (RMSE) = 17.34) (Figure a) (Agawin et al, ; Cloern & Dufford, ; Decembrini et al, ; Kim et al, ). Conversely, there was a higher proportion of nanophytoplankton (2.0–20.0 μm) and microphytoplankton (20.0–200.0 μm), which prefer nutrient‐rich environments (Koike et al, ; Lee et al, ; Probyn, ; Tremblay et al, ), and there was a slightly positive relationship between their abundance and coastal upwelling ( y = 13.28ln( x ) + 26.54, r 2 = 0.2376, RMSE = 9.664; and y = 11.21ln( x ) + 20.58, r 2 = 0.1134, RMSE = 12.75, respectively) (Figures b and c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…특히, 동해 울릉도 및 독도 해역은 동한난류와 북한한류가 교차함에 따라 북상하던 동한난류가 한국 연안으로부터 이안 되어 사행하며 (Hyun et al, 2009;Kim et al, 2014;Baek and Kim, 2018), 이 사행으로부터 첫 번째 마루에서 시계방 향으로 회전하는 울릉 난수성 소용돌이 (An et al, 1994;Lee and Niiler, 2010;Shin et al, 2005)와 독도 주변으로 동한 난류 사행의 첫 번째 골에서 반시계 방향으로 회전하는 독도 냉수성 소용돌이 (Mitchell et al, 2005b; (Wyrtki et al, 1976;Kang and Kang, 1990;Morimoto et al, 2000;Gordon et al, 2002;Lee and Niiler, 2005;Mitchell et al, 2005a;Shin et al, 2019 (Chang et al, 2002 (Shchepetkin and McWilliams, 2005). 수평 격자 체계는 격자 중심에 밀도, 수심, 수온을, 격자의 좌우에 유속의 동서 성분(u), 상하에 남북 성분(v)을 주어 계산의 안 정성과 효율성을 높인 Arakawa-C의 아격자체계를 사용하며 (Arakawa and Lamb, 1977), 수직 격자는 S-좌표계(Stretched terrain-following coordinate)를 사용한다 (Song and Wright, 1998;Shchepetkin and McWilliams, 2005 (Large et al, 1994)…”
unclassified